Comprehensive Physiology 2014
DOI: 10.1002/cphy.c130054
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the HPA Axis

Abstract: The hypothalamic-pituitary-adrenal (HPA) axis is a major component of the systems that respond to stress, by coordinating the neuroendocrine and autonomic responses. Tightly controlled regulation of HPA responses is critical for maintaining mental and physical health, as hyper- and hypo-activity have been linked to disease states. A long history of research has revealed sex differences in numerous components of the HPA stress system and its responses, which may partially form the basis for sex disparities in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
198
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(233 citation statements)
references
References 405 publications
19
198
0
2
Order By: Relevance
“…It is well known that adrenocortical activity in the rat, like in other mammals, is sensitive to androgens and estrogens [1,24,25]. These hormones may affect adrenal cortex growth and function either via central pathways (hypothalamic CRH and adenohypophyseal ACTH) or -with great probability -directly, via specific receptors expressed in the cortex and/or by interfering with adrenocortical enzymes, among them those involved in steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that adrenocortical activity in the rat, like in other mammals, is sensitive to androgens and estrogens [1,24,25]. These hormones may affect adrenal cortex growth and function either via central pathways (hypothalamic CRH and adenohypophyseal ACTH) or -with great probability -directly, via specific receptors expressed in the cortex and/or by interfering with adrenocortical enzymes, among them those involved in steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that function of adrenal cortex in various species is modulated by androgens and estrogens [1,24,25]. In vivo their action is mainly indirect and involves modulation of the hypothalamo-pituitary-adrenocortical axis, affecting primarily CRH and ACTH synthesis and/or secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that sex hormones are implicated in the glucocorticoid response to acute stress, and that females generally produce greater stress hormones when in the luteal phase of the menstrual cycle [18], changes in hormonal output associated with aging suggest that sex difference in inflammatory stress responses may more consistently emerge in older participants. Heightened pro-inflammatory stress responses may therefore be a relevant sex-specific risk marker in middle-and older-aged individuals, but most previous studies have mainly included young subjects.…”
mentioning
confidence: 99%
“…This is not surprising, given that sex differences in the development of HPA axis functioning have been well described previously [41,42] . Earlier analyses of the data used in the present study have revealed differential development of HPA axis functioning, with a tendency for attenuation among females during adolescence [29] .…”
Section: Discussionmentioning
confidence: 94%